Association of Increased Serum Lipopolysaccharide, But Not Microbial Dysbiosis, With Obesity‐Related Osteoarthritis. Issue 2 (4th January 2022) - Loeser, Richard F.; Arbeeva, Liubov; Kelley, Kathryn; Fodor, Anthony A.; Sun, Shan; Ulici, Veronica; Longobardi, Lara; Cui, Yang; Stewart, Delisha A.; Sumner, Susan J.; Azcarate‐Peril, M. Andrea; Sartor, R. Balfour; et al.
Abstract : Objective: To test the hypothesis that an altered gut microbiota (dysbiosis) plays a role in obesity‐associated osteoarthritis (OA). Methods: Stool and blood samples were collected from 92 participants with a body mass index (BMI) ≥30 kg/m 2, recruited from the Johnston County Osteoarthritis Project. OA patients (n = 50) had hand and knee OA (Kellgren/Lawrence [K/L] grade ≥2 or arthroplasty). Controls (n = 42) had no hand OA and a K/L grade of 0–1 for the knees. Compositional analysis of stool samples was carried out by 16S ribosomal RNA amplicon sequencing. Alpha‐ and beta‐diversity and differences in taxa relative abundances were determined. Blood samples were used for multiplex cytokine analysis and measures of lipopolysaccharide (LPS) and LPS binding protein. Germ‐free mice were gavaged with patient‐ or control‐pooled fecal samples and fed a 40% fat, high‐sucrose diet for 40 weeks. Knee OA was evaluated histologically. Results: On average, OA patients were slightly older than the controls, consisted of more women, and had a higher mean BMI, higher mean Western Ontario and McMaster Universities Osteoarthritis Index pain score, and higher mean K/L grade. There were no significant differences in α‐ or β‐diversity or genus level composition between patients and controls. Patients had higher plasma levels of osteopontin ( P = 0.01) and serum LPS ( P < 0.0001) compared to controls. Mice transplanted with patient or control microbiota exhibited a significant difference in α‐diversity ( P = 0.02) and β‐diversity, but no differences in OA severity were observed. Conclusion: The lack of differences in the gut microbiota, but increased serum LPS levels, suggest the possibility that increased intestinal permeability allowing for greater absorption of LPS, rather than a dysbiotic microbiota, may contribute to the development of OA associated with obesity.